2013
DOI: 10.3810/pgm.2013.03.2646
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Amlodipine/Olmesartan Medoxomil ± Hydrochlorothiazide in Patients Aged ≥ 65 or < 65 Years With Uncontrolled Hypertension on Prior Monotherapy

Abstract: Our subanalysis evaluated the efficacy of an amlodipine/olmesartan medoxomil (AML/OM)-based titration regimen to achieve blood pressure (BP) goals among patients aged ≥ 65 years. In this dose-titration study, 999 patients (228 of whom were aged ≥ 65 years) with uncontrolled BP after ≥ 1 month of monotherapy were switched to fixed-dose AML/OM 5/20 mg and uptitrated every 4 weeks to AML/OM 5/40 and 10/40 mg to achieve BP < 120/70 mm Hg. Patients were subsequently uptitrated every 4 weeks to AML/OM 10/40 mg + hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
3
7
1
Order By: Relevance
“…Results from this study indicate that the rate of ADRs was only slightly increased among patients who were over 65 years of age, and those with high cardiovascular risk. A study by Weir et al 18 of an FDC tablet of olmesartan/amlodipine with separate-pill HCT also indicated that age did not have a relevant influence on the ADR rate. Drug-related hypotension and orthostatic hypotension, however, occurred less frequently in patients aged greater than 65 years (2.2% and 0.0%) compared with under 65 years (2.3% and 0.3%).…”
Section: Discussionmentioning
confidence: 97%
“…Results from this study indicate that the rate of ADRs was only slightly increased among patients who were over 65 years of age, and those with high cardiovascular risk. A study by Weir et al 18 of an FDC tablet of olmesartan/amlodipine with separate-pill HCT also indicated that age did not have a relevant influence on the ADR rate. Drug-related hypotension and orthostatic hypotension, however, occurred less frequently in patients aged greater than 65 years (2.2% and 0.0%) compared with under 65 years (2.3% and 0.3%).…”
Section: Discussionmentioning
confidence: 97%
“…OM-AML tablets are an effective antihypertensive agent not only for the general population, but also for older patients, and patients with diabetes mellitus or obesity ( 22 , 23 ). Regarding the effect of OM-AML tablets on older patients with essential hypertension, a previous study demonstrated that the mean change of SeSBP/SeDBP was -14.5/-7.8 mmHg in older patients with uncontrolled hypertension who had previously received monotherapy followed by administration of OM-AML tablets for 20 weeks ( 24 ). Another study showed that after treatment with OM-AML tablets for 36 months, SeSBP/SeDBP decreased from 157.2/84.6 to 132.6/72.6 mmHg in older patients with hypertension ( 25 ), resulting in a mean change of -24.6/-12.0 mmHg for SeSBP/SeDBP.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of OM for the treatment of hypertension, both as monotherapy and as part of combination therapy, has been demonstrated across multiple patient subgroups in numerous hypertension studies. [7][8][9][10][11][12][13][14][15][16][17] Importantly, the findings of increased rates of cardiovascular death in OM-treated patients in ROADMAP and ORIENT are not supported by more recent large-scale retrospective cohort analyses, which observed no difference in risk between patients initiating OM and those initiating other ARBs or angiotensin-converting enzyme inhibitors. [18][19][20][21] Some concern for increased risk was raised with the use of high-dose olmesartan for �6 months' duration in elderly patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%